Le monde vu à travers les relations phrasales - Jamrozik, Elżbieta (Neophilologica, 2005)
Natural languages are characterized by the abundance of sentence structures used for the expression of logical relations between linguistic units. This abundance of structures has an internal hierarchy that depends on the complexity of these structures and on the degree of a connection between the elements of a clause: the same logical relation can be expressed by formally independent sentences, as well as by various forms of compound and complex sentences. The author of the article attempted to present, on the example of the Italian language, an internal hierarchy and various degrees of complexity of the logical relations between clauses. Some of these relations are primary (a cause and effect relationship) and demand the presence of linguistic exponents of relation to a lesser extent that those relations that are marked and demand the presence of certain logical exponents (condition, concession.) What is more, in the content of connectors one can isolate peripheral uses connected with a semantic core, which are, to a large extent, determined by context and pragmatic factors.